Assessment of saline water irrigation on biomass and quality of alfalfa: A sustainable agriculture perspective - Boyuan Lou; Yanzhe Hu; Teng Li; Qingsong Liu; Jintao Wang; Xinliang Dong; Liu Tian; Xuejia Zhang; Wenxin Bian; Tong Liu; Menghao Zhao; Hongyong Sun (Agricultural Water Management)
The lack of freshwater resources is a critical limiting factor for the crop production in the arid and semi-arid regions. Saline water irrigation presents a viable solution for addressing freshwater scarcity, particularly in North China Plain, by leveraging saline water resources to sustain crop production while minimizing soil salinity accumulation through seasonal rainfall leaching. This study assessed the effects of saline water irrigation (5.0 and 7.6 dS/m) on alfalfa biomass and quality across five irrigation amounts (20–100 mm) in 2022–2023. Results showed that reasonable saline water irrigation significantly enhanced alfalfa biomass and quality. Biomass increased markedly in the first two harvests (H1, H2) due to the irrigation but not in the latter two (H3, H4). The maximum biomass achieved at 60 mm (5.0 dS/m, 15.99 t/ha) and 76 mm (7.6 dS/m, 14.71 t/ha), representing 40.3 % and 24.3 % increases over rainfed controls. Early-season harvests (H1-H2) exhibited 10–67 % biomass enhancements primarily through stem growth (35–80 % contribution). CP was significantly increased at the H1 with irrigation of 60 mm (5.0 dS/m), whereas elevated salinity (7.6 dS/m) increased ADF and NDF content. Saline water irrigation elevated soil EC, while summer rainfall effectively leached salts, maintaining 0–40 cm soil salinity below alfalfa tolerance thresholds. Structural equation modeling quantified critical interactions: irrigation amount directly enhanced biomass while elevating soil EC, and water salinity indirectly reduced yield via EC accumulation. The optimal irrigation amounts were determined to be 51.0–72.3 mm for 5.0dS/m saline water and 58.3–76.0 mm for 7.6dS/m water, which balanced 20–40 % yield gains with stable interannual soil EC.